Problems of hemostasis in patients with persistent atrial fibrillation on the background of coronary heart disease (review article) (Eurasian Research Bulletin, 2023)
Ischemic heart disease (CHD) is still the most common disease worldwide, including Uzbekistan [1,2]. In terms of prevalence in the population after extrasystole, atrial fibrillation (AF) takes 2nd place. According to the data of domestic scientists of our country, among the population of Uzbekistan, cardiovascular diseases are the most common cause of death at 56%, and disability - 25%, which causes significant harm to the health of the nation and the state budget. Based on the results of population studies, about 11% of the population of the Republic over the age of 40 suffer from coronary artery disease [3]. The purpose of this study was to study new scientific literature and modern views on changes in the hemostasis system in coronary artery disease and ventricular fibrillation